2018
DOI: 10.1016/j.bjm.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons degradation by marine-derived basidiomycetes: optimization of the degradation process

Abstract: Pyrene and benzo[a]pyrene (BaP) are high molecular weight polycyclic aromatic hydrocarbons (PAHs) recalcitrant to microbial attack. Although studies related to the microbial degradation of PAHs have been carried out in the last decades, little is known about degradation of these environmental pollutants by fungi from marine origin. Therefore, this study aimed to select one PAHs degrader among three marine-derived basidiomycete fungi and to study its pyrene detoxification/degradation. Marasmiellus sp. CBMAI 106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 38 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…However, the remainder constituted those enzymes that were only detected (at low levels) in J3, indicating that trace aroma compounds were likely particularly associated with JF liquor flavor, such as ethyl benzeneacetate and benzaldehyde ( Xiao et al, 2016 ). Highly expressed members of these enzymes were mostly derived from fungal species in J3, which appears consistent with the contributions of some fungi toward the degradation of aromatic compounds ( Godoy et al, 2016 ; Sun et al, 2016 ; Vieira et al, 2018 ). Alternatively, enzymes expressed at low levels from bacteria may also substantively contribute to degradation of aromatic compounds ( Pérez-Pantoja et al, 2015 ; Van der Waals et al, 2017 ).…”
Section: Discussionsupporting
confidence: 75%
“…However, the remainder constituted those enzymes that were only detected (at low levels) in J3, indicating that trace aroma compounds were likely particularly associated with JF liquor flavor, such as ethyl benzeneacetate and benzaldehyde ( Xiao et al, 2016 ). Highly expressed members of these enzymes were mostly derived from fungal species in J3, which appears consistent with the contributions of some fungi toward the degradation of aromatic compounds ( Godoy et al, 2016 ; Sun et al, 2016 ; Vieira et al, 2018 ). Alternatively, enzymes expressed at low levels from bacteria may also substantively contribute to degradation of aromatic compounds ( Pérez-Pantoja et al, 2015 ; Van der Waals et al, 2017 ).…”
Section: Discussionsupporting
confidence: 75%
“…Sabino et al 33 reported on a large survey along the coast of Portugal in which they found dermatophytes only in a small proportion of samples. It is of interest that both Cryptococcus and Rhodotorula species, found in several beaches of the Israeli Mediterranean Coast, are Basidiomycetes, which have been described recently 34 as being able to degrade aromatic hydrocarbons that can be pollutants due to spill of petroleum in association with shipping. Cryptococcus uzbekistanensis was found in the sand beach of Ashdod, which is a major port of Israel.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, three additional enzyme families are produced by fungi for bio-remediation: Esterases, glutathione S-transferases (GSTs) and cytochrome P450 monooxygenase [227]. Accounting for this enormous set of enzymes, extremophilic marine fungi are suitable for the bioremediation of polluted saline environments due to their tolerance to high-salt conditions, thus becoming an essential resource in bioremediation of marine PAH-polluted environments [228,229] Some marine fungal species found in the Mediterranean and Red Sea DHABs, belonging to Aspergillus, Penicillium, Candida and Rhodotorula genera, have been reported to degrade some hydrocarbon compounds [230,231]. In particular, Rhodotorula glutinis identified in the DHAB L'Atalante has been reported to actively reduce oil compounds in petroleum polluted soils [232].…”
Section: Can Dhabs Fungi Be Exploited For the Bioremediation Of Pollumentioning
confidence: 99%